Liquid Chromatography Tandem Mass Spectrometry Detection of Ablmosechus manihot and Its Major Metabolites in Rat Urine After Oral Administration - Jiang, Weixing; Liu, Shuang; Wu, Bin; Huang, Chenggang (Asian Journal of Chemistry, 2010)
A highly specific and sensitive method using high performance liquid chromatographyelectrospray ionization (ESI) tandem ion trap mass spectrometry(HPLC-ESI-MSn) was developed to study on A. manihot and its metabolites in rat urine. The gradient elution reversed-phase HPLC system using water of 0.5 % formic acid and acetonitrile as gradient solvent mixtures was able to separate all metabolites of Ablmosechus manihot. The A. manihot were negative identified by the protonated molecules [M-H]– and further characterized by tandem mass spectrometric analysis with each it giving a characteristic collision induced dissociation product ion spectrum. Furthermore, 2 prototype constituents and 7 metabolites in urine were detected and elucidated. This convenient HPLC-MSn method could be used to identify the chemical components of extract of A. manihot as well as their metabolites and to reveal their possible metabolic mechanism of action in vivo.